RNA Binding Proteins Accumulate at the Postsynaptic Density with Synaptic Activity - Guoan Zhang; Thomas A. Neubert; Bryen A. Jordan (2012)
Neuronal activity elicits changes in synaptic composition that play an important role in experience-dependent plasticity (Choquet and Triller, 2003; Lisman and Raghavachari, 2006; Bourne and Harris, 2008; Holtmaat and Svoboda, 2009). We used a modified version of stable isotope labeling by amino acids in cell culture to identify activity-dependent modifications in the composition of postsynaptic densities (PSDs) isolated from rat primary neuronal cultures. We found that synaptic activity altered ∼2% of the PSD proteome, which included an increase in diverse RNA binding proteins (RNABPs). Indeed, 12 of the 37 identified proteins whose levels changed with synaptic activity were RNABPs and included the heterogeneous nuclear ribonucleoproteins (hnRNPs) G, A2/B1, M, and D. Knockdown of hnRNPs M and G using shRNAs resulted in altered numbers of dendritic spines, suggesting a crucial role for these proteins in spine density. Synaptic activity also resulted in a concomitant increase in dendritic and synaptic poly(A) mRNA. However, this increase was not affected by knockdown of hnRNPs M or G. Our results suggest that hnRNP proteins regulate dendritic spine density and may play a role in synaptodendritic mRNA metabolism.